To solve this, we must translate the sentence to an equation.
First, lets find an equation that can define all even integers.
Let [tex]n[/tex] be any integer (even or odd), then the equation for any even integer is:
[tex]2n[/tex]
Now, lets start with an arbitrary even integer [tex]2n[/tex], then the next even integer will be [tex]2(n+1)[/tex], and the next will be [tex]2(n+2)[/tex].
So, if we want the sum of three consecutive even integers to be 36 we write:
[tex]2n+2(n+1)+2(n+2)=36[/tex]
We can very easily solve for [tex]n[/tex]:
[tex]2n+2(n+1)+2(n+2)=6n+6=36[/tex]
[tex]6n=30[/tex]
[tex]n= \frac{30}{6}=5 [/tex]
So, [tex]n=5[/tex].
If we plug in 5 to the equations of our three consecutive even numbers we get that the numbers are 10, 12, and 14.